THE ROLE AND FUNCTIONAL RESPONSIBILITIES OF NURSES IN PROVIDING OUTPATIENT MEDICAL CARE TO WOMEN OF REPRODUCTIVE AGE AND PREGNANT WOMEN - Urazaliyeva I. R.; Ramanova D. Yu.; Djabarova Z. A. (Modern American Journals, 2026)
Outpatient medical services for women of reproductive age and pregnant women play a crucial role in improving maternal and child health outcomes. The effectiveness of these services largely depends on the professional activities and competencies of nurses working at the primary healthcare level. In modern healthcare systems, nurses are not only assistants to physicians but also independent specialists who perform essential functions in health promotion, disease prevention, early detection of risk factors, patient education, and continuous monitoring. During pregnancy, nurses maintain regular and systematic communication with women, provide antenatal and postnatal follow-up, support adherence to screening and preventive examinations, and offer counseling on medication use, nutrition, hygiene, and healthy lifestyle practices. Moreover, nursing interventions contribute to timely registration of pregnant women, early identification of complications, and strengthening psychological support, which enhances the quality and continuity of care in ambulatory settings. This article highlights the role and functional responsibilities of nurses in outpatient care, emphasizing their contribution to improving service quality, ensuring safe pregnancy monitoring, and promoting overall reproductive health.
Keywords: Outpatient care, nursing, reproductive health, pregnants, antenatal care, postnatal care, primary healthcare, health promotion, preventive services, patient counseling, risk factor, assessment, maternal and child health.